THE INTERDEPADANCE OF AGRICULTURAL DEVELOPMENT AND RURAL TOURISM - Petrović, Pero; Čerović, Slobodan (Economics of Agriculture, 2006)
Interdepadance of agricultural development and rural tourism in contemporary conditions will be more important. Agriculture has to provide human survival, as its goal, to provide food, necesary ror the people. In a process of agricultural production, people have changed natural environment ecological conditions. People needs are biger, not only nutritional, but the industrial needs of organic materials. Thats the agricurtural influence in ecosystem transformation. The way and the intensity of rural spaces and agriculturalland using have much more influence and circumstances on the society and country, than on each agricultural worker. The agrarian politics is a factor which should have, as its goal, providing wanted food quantities for domestic population as well as for the export. The agrarian politics have significant influence on the modern country management and enforcement of sustinable agriculture and healthy food production. In Serbia agriculture is not full protected and stimulated. So, theres need of agrarian politics transformation. In that kind of conditions, tourism development is directly dependingon agriculture and living environment protection. Rural tourism and sustainable development is very importante from aspect European integration process. Present state of our agrriculture and tourist industry clearly indicates the necesity to carry out the reform.